Review of research in learning environment - Ibrahim, Jamaiah (Faculty of Medicine, University of Malaya, 2008)
Educational environment of an institution is the environment experienced or perceived by students and teachers. Individual students and teachers will respond differently to these subtle elements in their learning experience. Curriculum's most significant manifestation and conceptualisation is the environment. There is a proven connection between the environment and the valuable outcomes of students' achievement, satisfaction and success. If one wants to describe, assess or get a handle on the curriculum in a medical school, then the educational and organisational environment or total milieu associated with the curriculum and the medical school needs to be studied. Educational environment is one of the most important determinants of an effective curriculum. Educational environment fosters scholarly or intellectual activities; it encourages friendliness, co-operation and supportiveness. It also fosters the learning, growth and development of students. Students' perceptions of their educational environment are a useful basis for modifying and improving the quality of educational environment. Several research groups over the years have attempted to identify and quantify the presence and impact of rather intangible aspects of a learning environment. Each study has used different survey questionnaires to solicit student reactions. (JUNMEC 2008; 11 (1): 7-11).